DISSOLUTION KINETICS AND ALTERATION OF EPIDOTE IN ACIDIC SOLUTIONS AT 25°C - Kalinowski B.E.; Faith-Ell C.; Schweda P. (My University, 1998)
The dissolution kinetics of epidote [Ca1.83Al2.00(Al0.11Fe0.743+Fe0.102+Mn0.001Mg0 .19Ti0.054+)Si3.00O12OH] were studied over the pH range 1-6.5 at 25°C using flow-through reactors. Ca and Si were found to be the most rapidly released elements in the structure, while Al and Fe tend to be retained. The Si-O-Al bonds are readily broken when protonated, resulting in release of Si-dimers and Si-tetrahedra, while the Al polymers are more resistant towards dissolution. Selective leaching of Ca produces a Ca-depleted rim with a thickness of 60-90 nm after 50-1000 h leaching depending on pH, whereas, Al and Fe are enriched in this zone. The calculated thickness of a Si-depleted rim is approximately 5-20 nm at pH=<2. After an initial growth period the thickness of the altered rim remains constant. However, Fe is selectively leached out together with Si and Ca in the pH 1 and 2 experiments, and as a result, Al alone constitutes the enriched layers at those conditions. Leaching of both Ca and Si is slowed down by the formation of this Al enriched layer, thus decreasing the dissolution process. Epidote dissolution rates based on Si release for one of the experimental series, are closely comparable with those of K-feldspar and micas. The reaction order with respect to H+ activity, was found to be 0.15 for grain size 5-20 μm and 0.44 for the 125-250 μm fraction. However, the dissolution stoichiometry is reversed for epidote compared with the silicates mentioned above, since Si is preferentially released over Al.
Keywords: EPIDOTE; KINETICS; WEATHERING; DISSOLUTION RATES; NONSTOICHIOMETRY